Initial Description of the Genome of Aeluropus littoralis, a Halophile Grass - Hashemi-Petroudi, Seyyed Hamidreza; Arab, Mozhdeh; Dolatabadi, Behnaz; Kuo, Yi-Tzu; Baez, Mariana Alejandra; Himmelbach, Axel; Nematzadeh, Ghorbanali; Maibody, Seyed Ali Mohammad Mirmohammady; Schmutzer, Thomas; Mälzer, Michael; Altmann, Thomas; Kuhlmann, Markus (Frontiers in Plant Science, 2022)
The use of wild plant species or their halophytic relatives has been considered in plant breeding programs to improve salt and drought tolerance in crop plants. Aeluropus littoralis serves as halophyte model for identification and isolation of novel stress adaptation genes. This species is described as perennial monocot grass. A. littoralis grows in damp or arid areas, often salt-impregnated places and waste land in cultivated areas. A. littoralis can survive where the water salinity is periodically high and tolerate high salt concentrations in the soil up to 1100 mM sodium chloride. Therefore, it serves as valuable genetic resource to understand molecular mechanisms of stress-responses in monocots. The knowledge can potentially be used for improving tolerance to abiotic stresses in economically important crops. Several morphological, anatomical, ecological, and physiological traits of A. littoralis have been investigated so far and also the transfer of stress related genes to other species resulted in enhanced stress resistance. After watering with salt water the grass is able to excrete salt via its salt glands. Meanwhile, a number of ESTs (expressed sequence tag), genes and promoters induced by the salt and drought stresses were isolated, sequenced and annotated at a molecular level. Here we describe the genome sequence and structure of A. littoralis analyzed by whole genome sequencing and histological analysis. The chromosome number was determined to be 20 (2n = 2X = 20), absence of B chromsomes shown, and the genome size calculated to be 354 Megabasepairs. This genomic information provided here, will support the functional investigation and application of novel genes improving salt stress resistance in crop plants. The utility of the sequence information is exemplified by the analysis of the DREB-transcription factor family.